Regional Variation in ADHD Treatment and Diagnosis Among Children and Adolescents in Denmark - Heidi Sonne; Anton Pottegård; Anna Sofie Kjærgaard Hansen; Mickael Bech; Helene Kildegaard (Basic & Clinical Pharmacology & Toxicology, 2026)
ABSTRACT Geographic variation in ADHD treatment and diagnosis among children and adolescents is well documented, yet the system‐level factors driving such differences remain poorly understood. We examined nationwide patterns of ADHD medication use and diagnoses in Denmark in 2024 and assessed whether municipal socioeconomy, regional hospital waiting times or private child psychiatrist capacity contributed to geographic variation. In this register‐based cross‐sectional study, we included all Danish residents aged 4–17 years using data from national registers. Pharmacological treatment was defined as at least one redeemed prescription for ADHD drugs, and diagnosis was defined as at least one hospital contact with ICD‐10 codes F90.x/F98.8. Prevalence was calculated overall and stratified by sex and age, with associations explored using Spearman's rank correlations and regression analyses. ADHD medication prevalence varied sixfold across municipalities (9.6–58 per 1000), with parallel variation in diagnoses (15–74 per 1000) and the largest differences observed among adolescents. Municipal socioeconomic status was weakly and inversely correlated with medication use (ρ = −0.20, p = 0.049), but not diagnoses. Neither waiting times nor specialist capacity was significantly associated with either outcome. Marked geographic variation in ADHD medication use and diagnoses persists in Denmark despite a uniform healthcare framework, and appears largely unexplained by the system‐level factors examined.